Drugs that increase gamma-aminobutyric acid transmission protect against the high pressure neurological syndrome. - Bichard, A. R. (Nature Publishing Group, 1982)
1 The effects on the high pressure neurological syndrome (HPNS) of drugs which facilitate gamma-aminobutyric acid (GABA) transmission were investigated. Threshold pressures for the onset of the behavioural signs of the HPNS in mice--tremors and convulsions were established. 2 Flurazepam hydrochloride 20 and 10 mg/kg and sodium valproate 800 and 400 mg/kg substantially raised the threshold pressures for both tremor and convulsions. 3 Amino-oxyacetic acid 35 and 25 mg/kg and diaminobutyric acid 600 mg/kg also significantly increased the thresholds. Muscimol 1 mg/kg (and 150 ng i.c.v.) was ineffective at non-toxic doses. 4 These effects paralleled the drugs' ability to raise the convulsion threshold to intravenous infusion of bicuculline in mice. 5 These results demonstrate that drugs with actions more selective than those of the general anaesthetics are effective against the HPNS. It is also possible that there is a GABAergic component to the effects of general anaesthetics on the HPNS.